A Comparison-Contrast of J. M. Keynes' Mathematical Modeling Approach in the General Theory with some of his General Theory Interpreters, especially J.E. Meade - Emmett Brady, Michael (History of economics review, 1996)
The analysis in this paper demonstrates that J M. Keynes' original mathematical model, presented in Chapters 10, 20-21 of the General Theory, is superior, in terms of mathematical completeness and rigor, to any other model put forward since 1936 which purports to give a technical exposition of "What Keynes Meant". This paper covers the mathematical models of Meade, Hicks, Harrod, Patinkin, and Barro-Grossman, as well as improved versions of the Meade model offered by Darity-Cottrell and Rappoport.